Feeding ecology of Brevoortia aurea larvae (Clupeidae, Alosinae) from Río de la Plata estuary off Uruguay (Ocean and Coastal Research, 2023)
This study analyses the feeding ecology of Brevortia aurea (Brazilian menhaden) larvae during a reproductive season in the Río de la Plata estuary (RPE), and explores its changes along larval development. Data were obtained from stomach content analyses of 205 individuals collected with a Bongo net during spring 2001. Larvae were discriminated into preflexion (PF), flexion (F) and post-flexion (PsF) stages. Feeding was described using complementary metrics like Feeding incidence (FI), the Relative Importance of different prey types consumed (IRI), the Degree of prey digestion (E) and Diet overlap (D), which were estimated and compared between stages. Also, larval morphometric relationships (body length, BL vs mouth width, MW) and between MW and maximum prey width (Wmax) were established for the range of observed larval sizes. The overall FI was 46.3% and increased with the development stage: 40.4% PF, 63.3% F, 78.6% PsF. Feeding occurred mainly during sunlit hours but no clear daily cycle could be established. Copepods and in particular Acartia tonsa were well represented among ingested preys, followed by invertebrate eggs and nauplii. Prey diversity and overlap between stages tended to decrease as development progressed. B. aurea exhibited isometric growth of MW in relation to BL. Average Wmax was 222.5 µm ± 100.9 SD, and increased non-linearly with both BL and MW. Gape size alone did not seem to be the limiting factor for prey choice (size), and we hypothesize that factors involved in the feeding mechanism other than mouth gape and linked with capture performance substantially influence the feeding ecology of this species in the RPE.